Altered functional connectivity in post-ischemic stroke depression: A resting-state functional magnetic resonance imaging study. Issue 100 (March 2018) - Zhang, Peiyao; Wang, Jing; Xu, Qin; Song, Zheng; Dai, Jianping; Wang, Jun
Abstract: Objective: In previous studies, post-stroke depression (PSD) was found to be related to stroke characteristics as well as social and psychological factors. This study identified altered functional connectivity (FC) in patients with PSD at the subacute phase in three brain networks: default mood network (DMN), cognitive control network (CCN), and affective network (AN). The correlation between FC and the severity of PSD was investigated. Materials and methods: Resting-state functional magnetic resonance image (rs-fMRI) was performed on 26 PSD patients (6 females), 24 stroke patients without depression (5 females), and 24 age-matched normal controls (6 females) all aged 40–75 years. The FC values of DMN, CCN, and AN were calculated and compared among the three groups. The Hamilton Depression Rating Scale (HDRS) (17 items) was employed and the score was correlated with FC in the PSD group. Results: The FCs of the three networks were altered in PSD patients at the subacute phase compared to stroke patients without depression and normal controls (NC). Moreover, the left inferior parietal gyrus, the left orbital part of inferior frontal gyrus, and left angular gyrus (which indicated altered FC) were significantly correlated with HDRS scores in PSD patients. Conclusions: Alteration of the three neural networks might be correlated with the development of PSD at the subacute phase of stroke.